2005
DOI: 10.1111/j.1600-0722.2005.00227.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental fear, regularity of dental attendance and subjective evaluation of dental erosion in women with eating disorders

Abstract: This questionnaire study, with a response rate of 53%, examined self-induced vomiting, erosions and dental attendance in women with eating disorders (EDs) as well as dental fear and its effect on attendance and communication with the dentist. A survey of 371 responding women with EDs, who were recruited from a self-help organization, revealed that dental fear was higher in women with EDs compared to the general population. Dental fear was present in 32.1% of women with EDs, and very high dental fear was presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 30 publications
0
38
1
2
Order By: Relevance
“…83 Willumsen reported that 75% of women who have reported abuse that included oral penetration had high levels of dental fear. 22,83 The ability of these individuals to accept minor or major discomfort associated with instru ments in the mouth was reduced and feeling unable to breathe and/or severe gagging or choking interfering with treatment delivery were increased. 71 It is also important to note that men who have experienced CSA are more likely than women to have experienced abuse involving oral sex.…”
Section: Dental Anxietymentioning
confidence: 99%
See 4 more Smart Citations
“…83 Willumsen reported that 75% of women who have reported abuse that included oral penetration had high levels of dental fear. 22,83 The ability of these individuals to accept minor or major discomfort associated with instru ments in the mouth was reduced and feeling unable to breathe and/or severe gagging or choking interfering with treatment delivery were increased. 71 It is also important to note that men who have experienced CSA are more likely than women to have experienced abuse involving oral sex.…”
Section: Dental Anxietymentioning
confidence: 99%
“…82 It is well reported that, although often suffering from poor self-esteem and confi dence, they need total control in stressful situ ations to be able to cope. 22,71,83 Dealing with dental treatment is difficult for all the reasons mentioned, plus the fact that the experience may provoke symptoms of post-traumatic stress, fl ashbacks and dissociation. 81 Interestingly, women who report dental fear and sexual abuse are often unaware that their dental fear may be related to the CSA.…”
Section: Dental Anxietymentioning
confidence: 99%
See 3 more Smart Citations